Gender Difference and The Predictive Role of Job Tension on Job Satisfaction Among Academic Staff in A Public University - Adekunle A Kenku; Dare Azeez Fagbenro; Abolade M Opatola (Psychocentrum Review, 2021)
Studies have investigated antecedents of job satisfaction, however, little is known about the predictive role of job tension on job satisfaction as well as gender difference on job satisfaction among academic staff in Nigeria. Using job demands–resources model as a theoretical framework, this study examined job tension on job satisfaction among selected academic staff of Nasarawa State University, Keffi. Participants were 75 (48 males and 27 females) academic staff with a mean age of 42.11 (SD of 4.12) recruited from six faculties in the university. Data were analyzed using simple linear regression and t-test for independent sample analysis. Results showed that job tension predict job satisfaction among academic staff. Also, female academic staff has higher level of job satisfaction than the male academic staff. The findings suggest that industrial and organisational psychologists should redesign academic job roles in such a way that it will devoid of stressful and tension socked pressure which will have positive implication for better job satisfaction among academic staff.